#EndRapeCulture Campaign in South Africa: Resisting Sexual Violence Through Protest and the Politics of Experience. (2nd January 2018) - Gouws, Amanda
ABSTRACT: This article analyses the #EndRapeCulture campaign in South Africa, where women students took to the streets in 2016 to protest against the pervasive normalisation of sexual violence on university campuses. In many cases, some participated topless and brandished sjamboks (whips) to show their resentment and anger at the prevailing conditions of sexual violence. The article looks at the role of digital media in circulating slogans around the campaign and asks the question whether these protests can be compared with SlutWalks or FEMEN. Another way of understanding the #EndRapeCulture campaign is to think through the implications of using experience as a form of identity politics.